Spindle Cell Carcinoma of the Larynx: A Confusing Diagnosis for the Pathologist and Clinician - Asli Bostanci; Gulay Ozbilim; Murat Turhan (Case Reports in Otolaryngology, 2015)
Laryngeal spindle cell carcinoma (SpCC) is an uncommon subtype of squamous cell carcinoma which represents 0.5% of all laryngeal squamous cell carcinomas. It is a biphasic tumor consisting of the combination of a malignant mesenchymal spindle cell component and a squamous cell component that includes dysplasia, carcinoma in situ, or invasive carcinoma. Although it has aggressive biological features, the probability of making a diagnosis in the early stages is high as it often leads to obstructive symptoms in the early period. Due to its low incidence, there is no clear consensus on prognostic factors and optimal treatment strategies yet. In this paper, a 60-year-old laryngeal SpCC case that was effectively treated with wide local excision followed by adjuvant radiotherapy was presented with the literature.